PENGARUH MOBILE ADVERGAME TERHADAP PERILAKU KONSUMEN (Studi Pada Remaja Usia 16 - 24 tahun di Kota Jakarta Selatan) - Hasna Ika Az-Zahra, (2023)
In the phenomenon of consumer behavior trends that have turned digital to meet consumer needs, marketers have changed their strategy of marketing products so that the products they market are not just dimmed. In this study, it will explore the phenomenon of advertising using the development of new media in which marketers use advertising in games. However, it is essentially a medium for entertainment and not a place for advertising. The research sought to see whether players could still be influenced by the advertising and decided to use the advertising's product (positive attitude), or the player simply took an interface in the game without regard to the advertising's product, so that the advertisers could use the advertising's product. Some people feel unaffected by advertising (negative content). This study used a quantitative research method with an exploratory approach that was done to teenagers aged 16 - 24 in South Jakarta. The sample in this study was 100 people with predetermined criteria. This study used the A-T-R theory (Awareness, Trial, and Reinforcement) with data retrieval techniques using questionnaires. The results of this study on the normality test showed that the data on this study were distributed abnormally because they had a significance value of 0.004 or <0.5. However, these two variabels are correlated with the correlation values in both variabels of 0.752 in the correlation test calculation. The regression calculation shows that F. calculation is 127,328 indicating that the two have interrelated significance values. The conclusion obtained in this study, that T.count found a value of 11.284 ± 1.984, meaning that in the T test that H0 was rejected and Ha accepted, then there is a significant influence of 56.55% on variabel X (mobile advergame) on variabel Y (consumer behavior) in purchasing skin products in advertisements in the Mobile Legendss game.